Perceptions of formal pharmacy leadership on the social role of the profession and its historical evolution: A qualitative study - Fernando de Castro Araújo-Neto; Aline Santana Dosea; Francielly Lima da Fonseca; Thaís Maria Araújo Tavares; Douglas de Menezes Santos; Déborah Mônica Machado Pimentel; Alessandra Rezende Mesquita; Divaldo Pereira de Lyra Jr (Elsevier, 2024)
Background: In recent years, pharmaceutical professionalism has been questioned due to the social role of pharmacy, which is ambiguous in the literature. This raises questions about the purpose of the profession among pharmacists, despite the efforts of their professional organizations and formal leaders to consolidate the occupational status of the profession. Objective: To understand the social role of pharmacy in Brazil through its historical evolution based on the perceptions of formal leaders of the profession. Methods: A qualitative study was conducted between July 2020 and February 2021 with pharmacists who held leadership positions in formal and professional pharmacy organizations in Brazil. The data obtained from the interviews were submitted to content analysis. Results: A total of 17 pharmacists participated in this study. The data analyzed presented perceptions about the social role of the pharmaceutical profession in Brazil, which promotes access to health through different means. These include the manager pharmacist, who facilitates access to public health policies; the caring pharmacist, who promotes health education and the rational use of medicines; and the technologist pharmacist, who researches, develops, and promotes access to safe and cost-effective medicines. The interviewees also discussed the evolution of this social role based on influential factors such as legislation, clinical movement, pharmaceutical education, labor market, behaviors, and attitudes of pharmacists. Conclusion: In this study, pharmaceutical professionalism was conceptualized based on its social role, which should be centered on the patient. Understanding such issues is part of the evolutionary purpose of the profession in Brazil and should be encouraged in the behaviors and attitudes of pharmacists despite the challenges faced by the profession.